RETORIKA BAHASA POLITIK RIDWAN KAMIL DALAM KONTESTASI HEGEMONI CALON GUBERNUR DKI JAKARTA 2024 - NEYSYA MEIVA AZIZA; ILHAM HERMAWAN; SHAFARENA ADITIA; ZALFIAN FAJRI; CAMELIA MARSANDA BR GINTING; I’IK DWI ANGGUN SARI (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research aims to 1Understand Ridwan Kamil's political communication rhetoric strategy as the 2024 DKI Jakarta Governor Candidate. 2Examine the public hegemony towards Ridwan Kamil's campaign as the 2024 Jakarta Governor, who previously served as the Governor of West Java. The main focus of this analysis includes rhetorical characteristics, political communication strategies, and their impact on public perception. This research uses a qualitative approach and literature study, with sources of information through news on iNews and other relevant news. 1The conclusion of this research shows that Ridwan Kamil's rhetoric as the 2024 DKI Jakarta Candidate reflects a complexity that can be explained through Aristotle's theory, which includes elements of ethos (credibility), logos (rational argumentation), and pathos (emotional influence). The political communication strategy applied is oriented towards efforts to establish hegemony, as explained in Gramsci's theory, which is reflected through inclusive narratives and efforts to accommodate the various interests of the people of Jakarta. Thus, creating relaxed communication by combining technical language and simple delivery, and being able to create emotional closeness with the audience. 2In the construction of political discourse built by Ridwan Kamil as the 2024 Jakarta Governor, he is able to create an image as a “modern metropolitan leader”, although there are still public doubts regarding the effectiveness of the implementation of the programs promoted. Public perception of Ridwan Kamil's leadership competence shows a positive trend, although the hegemony process has not been fully successful because there are groups that still refuse to provide support. This research provides a deeper understanding of the dynamics of political communication in the context of the 2024 DKI Jakarta Regional Head Election (Pilkada).